Instantaneous brain stroke classification and localization from real scattering data. Issue 3 (28th November 2018) - Salucci, Marco; Gelmini, Angelo; Vrba, Jan; Merunka, Ilja; Oliveri, Giacomo; Rocca, Paolo
Abstract: This work presents a 2‐step Learning‐by‐Examples approach for the real‐time classification of hemorrhagic/ischemic brain strokes and their successive localization from microwave scattering data collected around the human head. An experimental assessment against laboratory‐controlled data is performed to assess the potentialities of the proposed approach towards a reliable monitoring and instantaneous diagnosis clinic protocol.